Corrosion of Fe-25Cr-20Ni-0.40C alloy: an experimental and computational study - Lanz, César Armando (2016)
The investigation combines microstructura l characterization analyses and atomistic modeling to elucidate the mechanism of carburization embrittlement of an iron-nickel-chromium alloy expo sed to high temperature. It was studied an austenitic Fe-25Cr- 20Ni-0.40C stainless steel obtained of th e tubes of the industrial cracking furnace af ter 25,000 h of servi ce at 900-1200 ºC. T he service-exposed material presented bigger carbides in the aust enitic matrix comparing with the as-cast material, cavities betwe en the grains and micro fissures in grain edges, indicating that th e material present damage by creep. The theoretical calculation s help us to interpret the changes in the alloy electronic structure and the chemical bonding. The atomic orbital occupations of the metallic bonds are affected during carburization. The strengths of the, Cr-Ni, Fe-Cr, Fe-Ni and Ni-Ni bonds nearest neighbors t o the carbon atoms are the most affected. The metallic bond weakening is mainly a consequence of the new C-Ni, C-Fe and C-Cr interactions formed after carburization phenomena.